STRATEGI PEMBELAJARAN INOVATIF UNTUK ANAK USIA DINI: SEBUAH STUDI LITERATUR TERPILIH UNTUK PENCAPAIAN GLOBAL - Anne Effane; Asri Humaira, Megan; Rina Feriana (Jurnal Ilmiah Edukatif, 2024)
This study explores innovative learning strategies for early childhood that aim to improve global attainment. The research method undertaken was literature. By reviewing selected literature, this study highlights the importance of integrating technology, project-based learning and play activities in the early education curriculum. The review showed that these approaches can increase children's engagement and develop important skills such as critical thinking and problem-solving. However, there are significant challenges such as limited access to technology in remote areas and a lack of training for educators. This research emphasises the importance of collaborative support from government, parents and communities to overcome these barriers. With concerted efforts, this innovative learning strategy can effectively prepare children to face the global demands of the future.